(untitled) (Research, Society and Development, 2022)
Sites of severe stress can cause changes of great impact on the ontogenetic development of organisms. Floating Asymmetry (PA) is a tool that is characterized by indicating instabilities and plasticities caused by disturbances of the environment in which the plants are inserted. This research aimed to evaluate whether or not there is PA in 600 folyols of Individuals of S. terebinthifolia collected randomly in four public places in the municipality of Arapiraca-AL. The right and left sides of these web stools were measured and the measurements were submitted to the Shapiro-Wilk test, which did not indicate the existence of PA for the folíolos analyzed in this study, because the data differed from the normal distribution (W = 0.46393 p<2.2e-16). PA was not accurate in plant bioindication, since the species S. terebinthifolia presents a certain resistance and great adaptability to stressful environments, not presenting morphological responses such as leaf floating asymmetry.